Management of Bleeding in Exclusive Endoscopic Ear Surgery: Pilot Clinical Experience. (5th September 2017) - Anschuetz, Lukas; Bonali, Marco; Guarino, Pierre; Fabbri, Filippo B.; Alicandri‐Ciufelli, Matteo; Villari, Domenico; Caversaccio, Marco; Presutti, Livio
Abstract : Objective: Transcanal exclusive endoscopic ear surgery requires the management of the endoscope and the surgical instruments in the external auditory canal. Bleeding in this narrow space is one of the most challenging issues, especially for novice endoscopic ear surgeons. We aim to assess the severity and occurrence of bleeding and describe strategies to control the bleeding during endoscopic ear surgery. We hypothesize that bleeding is reasonably controllable in endoscopic ear surgery. Study Design: Case series with chart review. Setting: Tertiary referral center. Subjects and Methods: We retrospectively assessed 104 consecutive cases of exclusive endoscopic ear surgery at the University Hospital of Modena, Italy. The surgical videos and the patient charts were carefully investigated and analyzed. Results: Hemostatic agents included injection of diluted epinephrine (1:200, 000, 2% mepivacaine), cottonoids soaked with epinephrine (1:1000), mono‐ or bipolar cautery, washing with hydrogen peroxide, and self‐suctioning instruments. The localization of bleeding in the external auditory canal was most frequently the posterior superior part, and inside of the middle ear, it was the pathology itself. Statistical analysis revealed significant differences comparing the mean arterial pressure and the type of intervention among bleeding scores. Conclusion: The management of bleeding in endoscopic ear surgery is feasible through widely available hemostatic agents in reasonable frequency. This study gives an instructive overview on how to manage the bleeding in the exclusive endoscopic technique. Even the highest bleeding scores could be managed in an exclusively endoscopic technique.